Factors Affecting Lao PDR's Sustainable Development Goal (SDG 2) of Achieving Food Security - lorthongloay, seechance; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purpose of this study were:1) to investigate the proportion of the population experiencing hunger in the Lao PDR, and 2) to analyze the factors affecting Lao PDR's Sustainable Development Goal 2 (SDG 2) of achieving food security The study draws on annual data from the World Bank and the Food and Agriculture Organization of the United Nations for the years 2001 to 2024 The EViews 9 program was used to determine the correlation between independent variables and to estimate the multiple regression equations via the Least Squares method The result found that: 1) The proportion of the population experiencing hunger in the Lao PDR showed a continuous downward trend from 2001 to 2024 However, this figure increased during the pandemic era, with the COVID-19 outbreak serving as a primary driver of this trend. 2) Factors affecting Lao PDR's Sustainable Development Goal 2 (SDG 2) of achieving food security with statistical significance at 0.1 level, consist of five factors, such as: agriculture share of total government expenditure, agricultural land, total official flows (disbursements) for agriculture, population growth, and the proportion of population suffering from hunger in last year. The equation of predictive power was at 98.88 % points.